الإغتراب الوظيفي وتأثيره على الأداء الوظيفي للعمال في المؤسسة - قواسمية العلمي; بلكرم قطرالندى (University of Eloued جامعة الوادي, 2024)
تسعى كل مؤسسة الى تحقيق الأهداف التي تأسست من أجلها، ويكون ذلك من خلال الاستخدام الامثل للموارد المتاحة من موارد بشرية، مالية، تجهيزات ووسائل، وهذا ما نجده في البلديات عبر كافة ارجاء ومناطق الوطن، ولكن هناك بعض المشاكل التي يمكن ان تعيق أداء العمال، ومن بين هذه المعوقات نجد الاغتراب الوظيفي الذي يمكن ان يؤثر على أداء العمال. هدفت هذه الدراسة للتعرف على الاغتراب الوظيفي وتأثيره على الأداء الوظيفي لموظفي بلدية المزرعة ولاية تبسة، حيث اعتمدنا على المنهج الوصفي، وعلى استمارة الاستبيان كأداة لجمع البيانات، وكانت عينة الدراسة عينة عشوائية بسيطة تقدر ب25 موظف من موظفي بلدية المزرعة، وقد توصلت هذه الدراسة الى ان الاغتراب الوظيفي له أثر سلبي على اداء العاملين الوظيفي في بلدية المزرعة ولاية تبسة، حيث انه كلما زاد الشعور بالاغتراب كلما انخفض مستوى الأداء. Abstract: Every institution seeks to achieve the goals for which it was established, and that is through the optimal use of available resources in terms of human, financial, equipment and means, and this is what we find in municipalities across all parts and regions of the country, but there are some problems that can hinder the performance of workers, Among these obstacles, we find job alienation, which can affect the performance of workers. This study aimed to identify job alienation and its impact on the job performance of the employees of the municipality of Mazraa, Tebessa, where we relied on the descriptive approach, and on the questionnaire as a tool for data collection, and the study sample was a simple random sample estimated at 25 employees. Negative on the job performance of the workers in the municipality of Mazraa, Tebessa, as the greater the feeling of alienation, the lower the level of performance.
دراسة ميدانية ببلدية المزرعة
Keywords: اغتراب; اغتراب وظيفي; أداء; أداء وظيفي; بلدية; Alienation; functional alienation; performance; functionality; municipality